2021
DOI: 10.1097/md.0000000000024671
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomarker for predicting sepsis mortality

Abstract: The mortality rate of patients diagnosed with sepsis is high. To date, many markers in sepsis patients have been studied to diagnose, determine their prognosis, and contribute to treatment. These studies were conducted in both experimental and clinical settings, but clinical trials remain limited. Therefore, more well-planned clinical studies are needed in patients with sepsis. The current study aimed to examine the prognostic role of signal peptide-CUB-epidermal growth factor-like domain-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The sole gene downregulated by R, SCUBE1, a cell surface glycoprotein found in platelet and endothelial cells [87], was particularly interesting. A very recent study [88] has demonstrated that SCUBE1 is an independent prognostic factor in septic patients, and positive correlates with accepted inflammatory biomarkers and "Acute Physiology And Chronic Health Evaluation II" (APACHE-2), a severity-of-disease classification system [89]. Moreover, accumulation of this protein in blood is associated with vascular dysfunctions like atherosclerotic lesions or ischemic stroke [90], and ovarian impairment [91,92].…”
Section: Resveratrol Transcriptional Effectsmentioning
confidence: 99%
“…The sole gene downregulated by R, SCUBE1, a cell surface glycoprotein found in platelet and endothelial cells [87], was particularly interesting. A very recent study [88] has demonstrated that SCUBE1 is an independent prognostic factor in septic patients, and positive correlates with accepted inflammatory biomarkers and "Acute Physiology And Chronic Health Evaluation II" (APACHE-2), a severity-of-disease classification system [89]. Moreover, accumulation of this protein in blood is associated with vascular dysfunctions like atherosclerotic lesions or ischemic stroke [90], and ovarian impairment [91,92].…”
Section: Resveratrol Transcriptional Effectsmentioning
confidence: 99%
“…The Sequential Organ Failure Assessment (SOFA) score was used for predicting deaths in patients with sepsis in the ICU. A score of two or more was considered a predictor of mortality in sepsis patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The Sequential Organ Failure Assessment (SOFA) scoring system has been used to diagnose patients with sepsis in the ICU and determine their prognosis. [ 5 – 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The Acute Physiology and Chronic Health Evaluation 2 (APACHE-2) scoring system is frequently used in several hospitals. The Sequential Organ Failure Assessment (SOFA) scoring system has been used to diagnose patients with sepsis in the ICU and determine their prognosis [5–7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation